Association between 24-hour urine volume and 28-day intensive care unit mortality in sepsis patients: a multi-center retrospective cohort study - Lin, Yuzhan; Lin, Weiguo; Fu, Cheng; Sun, Ruixue; Hong, WeiLi; Chen, Xinglin; Yan, Shaorong (Frontiers in Medicine, 2024)
Background: Sepsis is defined as a dysregulated host response to infection that results in life-threatening organ dysfunction. The 24-hour urine volume plays a crucial role in assessing the prognosis of septic patients. This study aims to investigate the relationship between 24-hour urine volume and 28-day intensive care unit (ICU) mortality in septic patients and exploring the dose-response relationship between these variables. Methods: This retrospective cohort study analyzed data from 7,218 sepsis patients in the eICU Collaborative Research Database. Logistic regression models and generalized additive models were used to examine the relationship between 24-hour urine volume and 28-day ICU mortality. Results: A negative correlation was found between 24-hour urine volume and ICU 28-day mortality. In the fully adjusted model, each 50 mL increase in 24-hour urine volume significantly reduced mortality risk by 1% (OR = 0.99, 95% CI = 0.98-0.99, P < 0.001). A nonlinear dose-response relationship was observed, with an inflection point at approximately 1663.5 ml. Below this threshold, increased urine volume was significantly associated with reduced mortality risk (OR = 0.97, 95% CI: 0.96-0.98, P < 0.001), while above this point, the relationship was not statistically significant. Conclusion: This study demonstrates a nonlinear negative correlation between 24-hour urine volume and 28-day ICU mortality in sepsis patients. Keywords: Dose-response relationship, intensive care unit, mortality, sepsis, urine volume